Gamified interventions to improve the knowledge, attitude and practice on rational use of antibiotics among school children in Mysuru, South India, to curb the growing antimicrobial resistance (AMR) - Sumana, Mahadevaiah Neelambike; Shettar, Supreeta R.; Maheshwarappa, Yogeesh D.; Megha, G. K.; G. S., Veerabhadra Swamy; Shylaja Eshwarappa, Chinchana; S. C., Shruthi Shree (Frontiers in Public Health, 2025)
BackgroundAntimicrobial resistance (AMR) is a global emergency, and the general public and School children are limited in their awareness of the rational use of antibiotics. Gamified education can effectively address this issue. This study aimed to improve knowledge, attitudes, and practices regarding rational antibiotic use through innovative games.MethodologyA gamified educational intervention was conducted with 2,195 high school students (13–16 years) in Mysuru, South India. The session included a blackboard introduction to microbes and antibiotics, an animated video on irrational antibiotic use, and games like Bucketing the Ball and Monkeying with Donkey to teach when antibiotics are unnecessary (e.g., respiratory tract infections and gastroenteritis). Pre- and post-test questionnaires were administered and analysed.ResultsResults showed significant improvements: knowledge of antibiotic effects increased from 2.5 to 82.5%; understanding of antibiotics for bacterial infections rose from 11.5 to 82.5%; awareness of when to avoid antibiotics for common infections improved from 5.1 to 96.77%; and awareness of their use for urinary, skin, and soft tissue infections increased from 19.6 to 90.38%. Practices like not buying antibiotics without a prescription and completing the course improved from 20.3 to 91.92%.ConclusionGamified education effectively enhances knowledge, awareness, and practice of rational antibiotic use. With rising AMR, such innovative interventions are crucial to educating the general public and School children, ensuring a long-lasting impact on this global issue.